The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4314/sajas.v51i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing soybean meal with slow-release urea on milk production of Holstein dairy cows

Abstract: The study investigated the effects of replacing soybean meal (SBM) with slow-release urea (SRU) on milk production, milk composition, and rumen fermentation of Holstein dairy cows. Sixteen Holstein cows weighing between 550 and 680 kg in mid lactation were randomly assigned to four dietary treatments in a 12-week study. The treatments consisted of T1: a diet containing 16.7% crude protein (CP), T2: T1 with 0.5% SRU replacing plant protein, T3: T1 with 0.75% SRU replacing plant protein, and T4: T1 with 1.00% SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
2
4
2
Order By: Relevance
“…Reproductive performance remained unaffected by the treatment ( Table 2 ), which is in agreement with the findings of Hallajian et al (2021), who reported similar characteristics of the follicles, blood levels of progesterone, and milk urea nitrogen (MUN) between dairy cows fed exclusively with SBM or with the partial replacement of SBM, SRU [ 32 ]. These results show that feeding with SRU appears to overcome the possible negative effect of other NPN sources, such as feed grade urea, on both plasma urea nitrogen and overall reproductive performance [ 33 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Reproductive performance remained unaffected by the treatment ( Table 2 ), which is in agreement with the findings of Hallajian et al (2021), who reported similar characteristics of the follicles, blood levels of progesterone, and milk urea nitrogen (MUN) between dairy cows fed exclusively with SBM or with the partial replacement of SBM, SRU [ 32 ]. These results show that feeding with SRU appears to overcome the possible negative effect of other NPN sources, such as feed grade urea, on both plasma urea nitrogen and overall reproductive performance [ 33 ].…”
Section: Resultssupporting
confidence: 90%
“…Average weekly milk production in the two groups (a = p-value ≤ 0.05; x = p-value ≤ 0.1).Conversely,Galo et al (2003) [30], andGiallongo et al (2015) [31], did not show any gain in milk production when SBM was partially replaced by SRU.In the present study, DMI was significantly reduced in the treatment group (23.92 vs. 24.69 kg/head/d in control) (p = 0.04), positively affecting FCR. In fact, the FCR significantly improved (p < 0.0001) during treatment with an overall increase in feed efficiency at 6.9% due to the lower DMI and better milk production.These results agree with the findings ofSalami et al (2021), who reported a 3% enhancement in feed efficiency due to a significant reduction in feed intake without any effects on milk yield when the traditional protein sources were replaced with SRU in dairy cows' diets in Northern Europe[8].Reproductive performance remained unaffected by the treatment (Table2), which is in agreement with the findings ofHallajian et al (2021), who reported similar characteristics of the follicles, blood levels of progesterone, and milk urea nitrogen (MUN) between dairy cows fed exclusively with SBM or with the partial replacement of SBM, SRU[32]. These results show that feeding with SRU appears to overcome the possible negative effect of other NPN sources, such as feed grade urea, on both plasma urea nitrogen and overall reproductive performance[33].Body condition scores were not influenced by the treatment (Table2).…”
supporting
confidence: 92%
See 3 more Smart Citations